2022
DOI: 10.1007/s00113-022-01263-z
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der COVID-19-Pandemie auf die Frakturepidemiologie am Beispiel der Tibiaplateaufraktur

Abstract: Hintergrund Während der Coronawellen wurde durch Maßnahmen wie Kontaktbeschränkungen, Lockdown und Verschiebung von planbaren Operationen versucht, das Gesundheitssystem zu entlasten. In der Bevölkerung führten diese Maßnahmen zu einer Änderung des Freizeitverhaltens sowie des Individualverkehrs. Ziel der Arbeit Diese Arbeit untersucht epidemiologische Daten der Tibiaplateaufraktur (TPF) vor und während der Pandemie und inwieweit sich pandemiebekämpfende Maßnahmen auswi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In view of the disparity between patients' perceptions and actual outcomes, there is a pressing need for comprehensive research that analyzes the true patient-reported data regarding proximal tibial plateau fractures, particularly given the significant increase in TPFs [4,22]. By gaining a deeper understanding of the functional limitations and recovery trajectories associated with these fractures, surgeons can better inform patients about the expected outcomes and assist them in making well-informed decisions regarding their treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the disparity between patients' perceptions and actual outcomes, there is a pressing need for comprehensive research that analyzes the true patient-reported data regarding proximal tibial plateau fractures, particularly given the significant increase in TPFs [4,22]. By gaining a deeper understanding of the functional limitations and recovery trajectories associated with these fractures, surgeons can better inform patients about the expected outcomes and assist them in making well-informed decisions regarding their treatment options.…”
Section: Introductionmentioning
confidence: 99%